2008
DOI: 10.1111/j.1748-1716.2008.01834.x
|View full text |Cite
|
Sign up to set email alerts
|

Flow‐mediated dilation and exercise‐induced hyperaemia in highly trained athletes: comparison of the upper and lower limb vasculature

Abstract: Therefore, in the upper as well as in the lower limb vasculature, repetitive exposure to increased shear stress over a long-term period results in improved FMD of large conduit arteries as well as greater vasodilatory capacity during isolated exercise in the predominantly trained muscles. Long-term training involving predominantly the lower limbs also results in enhanced vascular reactivity in upper limb conduit and resistance vessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 40 publications
2
55
2
Order By: Relevance
“…Therefore, it is possible that the cutaneous circulation at different anatomical locations may reflect the functional impairments in related macrovascular beds. Previous studies have reported less responsive macrovascular beds in the legs than in the arms (10)(11)(12). Aging (12,13) and peripheral arterial disease (14) significantly reduces the reactivity of the lower limbs.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, it is possible that the cutaneous circulation at different anatomical locations may reflect the functional impairments in related macrovascular beds. Previous studies have reported less responsive macrovascular beds in the legs than in the arms (10)(11)(12). Aging (12,13) and peripheral arterial disease (14) significantly reduces the reactivity of the lower limbs.…”
Section: Introductionmentioning
confidence: 97%
“…The attenuated endothelium dependent vasodilatation has been found in the upper extremities of subject during acute rise in blood pressure induced by hydrostatic factor (17). Despite the significant work performed on the primary conduit vessels of the arm and leg to assess limb vascular heterogeneity (10)(11)(12)(13)17), only one single work (7) compared upper and lower limb cutaneous vascular function in humans. And, there are currently no data comparing cutaneous blood flow recorded from upper and lower limbs in EHT patients.…”
Section: Introductionmentioning
confidence: 99%
“…63 FMD was also higher in healthy athletes at the end of a period of intensive training, when compared to baseline. 64 In a randomized clinical trial, supervised exercise training in patients with PAD increased their 6-minute walk distance by 36 meters and their treadmill walking time by 3.44 minutes, while improving their FMD by 1.57%, compared to controls. 19 The contributions of decreased arterial stiffness and improved endothelial function in the improvement in exercise performance observed in PAD patients who undergo exercise training is therefore plausible, and amenable to testing in a clinical trial.…”
mentioning
confidence: 99%
“…However, our results show significant decrease in resistance in both the sum of the upper limbs and the sum of the lower limbs indicating a fluid shift that is related to the fluid consumed (water) by the subjects, but independent of tonicity. Whole body aerobic exercise such as treadmill walking elicits changes in blood flow directly related to muscle recruitment and the intensity of the activity [26]. The increase in muscle blood flow is mediated through local and central vasodilators.…”
Section: Discussionmentioning
confidence: 99%